2015
DOI: 10.1093/brain/awv215
|View full text |Cite
|
Sign up to set email alerts
|

Clinical correlates of raphe serotonergic dysfunction in early Parkinson’s disease

Abstract: Post-mortem and neuroimaging studies suggest that the serotonergic system, which originates from the brainstem raphe nuclei, is disrupted in Parkinson's disease. This could contribute to the occurrence of non-motor symptoms and tremor, which are only partially explained by dopamine loss. However, the level of involvement of the serotonergic raphe nuclei in early Parkinson's disease is still debated. (123)I-FP-CIT single photon emission computed tomography is a marker of dopamine and serotonin transporter avail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
114
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 180 publications
(124 citation statements)
references
References 41 publications
(54 reference statements)
5
114
0
5
Order By: Relevance
“…Of the 38 studies on depression, 33 reported findings from one single imaging modality: 19 used either PET [11, 12, 13,15, 16, 17, 18, 19] or SPECT 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30 techniques, four used T1‐weighted imaging 31, 32, 33, three used DTI 34, 35, 36, six used resting state functional MRI (RS‐FMRI) 37, 38, 39, 40, 41, 42 and two used TCS methods 43, 44. The remaining four of the 38 studies reported findings from structural T1‐weighted imaging plus another imaging method, including PET 14, DTI 45, task FMRI 46 and RS‐FMRI 47, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Of the 38 studies on depression, 33 reported findings from one single imaging modality: 19 used either PET [11, 12, 13,15, 16, 17, 18, 19] or SPECT 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30 techniques, four used T1‐weighted imaging 31, 32, 33, three used DTI 34, 35, 36, six used resting state functional MRI (RS‐FMRI) 37, 38, 39, 40, 41, 42 and two used TCS methods 43, 44. The remaining four of the 38 studies reported findings from structural T1‐weighted imaging plus another imaging method, including PET 14, DTI 45, task FMRI 46 and RS‐FMRI 47, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The serotonergic system is altered from the early stages of Parkinson's disease A growing body of evidence, provided by neuroimaging studies, points towards global serotonergic disruption in Parkinson's disease (Doder et al, 2003;Boileau et al, 2008;Pavese et al, 2010;Politis et al, 2010b;Ballanger et al, 2012;Qamhawi et al, 2015).…”
Section: Location Of the Main Brain Areasmentioning
confidence: 99%
“…This may be because most of the neuroimaging studies performed so far have included patients with Parkinson's disease who have been treated chronically with dopaminergic medication or have been exposed to serotonergic drugs, which may consequently hinder the pathophysiological interpretation of the associated results (Brooks et al, 1990;Doder et al, 2003;Kerenyi et al, 2003;Remy et al, 2005;Weintraub et al, 2005;Albin et al, 2008;Boileau et al, 2008;Pavese et al, 2010;Politis et al, 2010a, b;Thobois et al, 2010;Strecker et al, 2011;Ballanger et al, 2012;Joutsa et al, 2015). In addition, the delineation of nonmotor signs is not always detailed, which limits the clinical interpretation of these investigations (Qamhawi et al, 2015). Furthermore, post-mortem and neuroimaging studies performed in early-stage patients have sometimes reported conflicting results, either showing serotonergic disruption at Parkinson's disease onset (Albin et al, 2008;Politis et al, 2010a;Joutsa et al, 2015;Qamhawi et al, 2015) or not (Beucke et al, 2011;Strecker et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cardinal pathological characteristic of PD is the progressive loss of dopaminergic neurons in the substantia nigra pars compacta [7], however, lines of evidence from in vivo molecular imaging research has demonstrated that PD pathology involves also non-dopaminergic systems such as the serotonergic [8][9][10]. Serotonergic pathology in PD has been associated with the development of tremor [11,12], dyskinesias [13][14][15] and various non-motor symptoms [16][17][18].…”
Section: Introductionmentioning
confidence: 99%